Analysis and recommendations development for improvement of active chemical enterprise integrated management system. - E. V. Guschin; E. G. Khomutova; V. V. Borisova (Тонкие химические технологии)
The integrated management system (IMS) process model of Saratovorgsintez, Ltd. has been built. The system includes quality management subsystem, environmental protection subsystem, employment protection subsystem. Probable fields for improvement of Saratovorgsintez, Ltd. system has been shown. IMS improvement recommendations has been also developed.